Both total testosterone and sex hormone‐binding globulin are independent risk factors for metabolic syndrome: results from Fangchenggang Area Male Health and Examination Survey in China. Issue 5 (5th July 2013) - Zhang, Jiange; Huang, Xianghua; Liao, Ming; Gao, Yong; Tan, Aihua; Yang, Xiaobo; Zhang, Haiying; Mo, Linjian; Zhang, Youjie; Lu, Zheng; Wu, Chunlei; Hu, Yanling; et al.
Abstract Background Metabolic syndrome is often beneficial from testosterone replacement therapy. Although testosterone and sex hormone‐binding globulin (SHBG) are inversely associated with the risk of metabolic syndrome, it is controversial whether the association between testosterone and metabolic syndrome is independent of SHBG. Methods Testosterone, SHBG and metabolic syndrome were evaluated in 2361 men aged 20–73 years, who participated in the population‐based Fangchenggang Area Male Health and Examination Survey. Total testosterone, SHBG and other biochemical profiles were measured. Free testosterone and bioavailable testosterone were calculated on the basis of Vermeulen's formula. Metabolic syndrome was defined according to the National Cholesterol Education Program Adult Treatment Panel III criteria for Asian population. The independent associations with metabolic syndrome were determined by multivariate logistic regression analysis. Results Men with metabolic syndrome had a lower level of total testosterone, bioavailable testosterone, free testosterone, or SHBG than those without metabolic syndrome (all p < 0.001). Both total testosterone and SHBG were inversely correlated with body mass index or homeostasis model assessment of insulin resistance (all age‐adjusted p < 0.001). Men within the lowest quartile of total testosterone [odds ratio (OR) = 4.86, 95% confidence interval (CI) = 2.72–8.68], bioavailable testosterone (OR = 3.04, 95% CI = 1.81–5.10), free testosterone (OR = 3.08, 95% CI = 1.81–5.27) or SHBG (OR = 4.28, 95% CI = 2.52–7.27) had a risk of metabolic syndrome after adjusting for age, smoking, homeostasis model assessment of insulin resistance and body mass index. Total testosterone remained inversely associated with metabolic syndrome after further adjusting for SHBG (OR = 0.95, 95% CI = 0.92–0.99), while SHBG remained inversely associated with metabolic syndrome after further adjusting for total testosterone (OR = 0.99, 95% CI = 0.97–1.00). Conclusion Total testosterone and SHBG are independent risk factors of metabolic syndrome. Prospective studies are needed to explore whether the association between sex hormones and metabolic syndrome was mediated by insulin resistance or obesity. Copyright © 2013 John Wiley & Sons, Ltd.